DINAMIKA SPASIAL PEMANFAATAN LAHAN OLEH MASYARAKAT DAERAH ALIRAN SUNGAI (DAS) KREO - Setyowati, Dewi Liesnoor (Faculty of Social Science, Universitas Negeri Semarang, 2009)
Landuse dynamics of Kreo watershed from the result of interpretation of satellite image landsat (theÃ‚Â year 1994) and image SPOT-5 (the year 2006) in the form of degradation of open farm wide of 67,07%,Ã‚Â coppice 9,61%, forest 6,69%, and rice feld 4,64%; improvement of plantation wide 24,42%, setlementÃ‚Â 21,68%, and mixture garden with a width of 1,05%. Forest wide and plantation of DAS Kreo only with aÃ‚Â width of 17,19% had not pursuant to ideal wide of minimum forest of 30% at one particular in watershedÃ‚Â (PP number 33 Ã‚Â the year 1970). Wide area of setlement Ã‚Â in Kreo watershed with a width of 12,21% Ã‚Â isÃ‚Â including category has exceeded ideal boundary of setlement area at one particular in watershed, maximumÃ‚Â boundary (threshold) in the form of area of waterproof equal to 6%-10% in Ã‚Â watershed.Keywords: Landuse spatial dynamic, landuse trend.